Distinct Seasonal Patterns of Bacterioplankton Abundance and Dominance of Phyla α-Proteobacteria and Cyanobacteria in Qinhuangdao Coastal Waters Off the Bohai Sea - Yaodong He; Biswarup Sen; Shuangyan Zhou; Ningdong Xie; Yongfeng Zhang; Jianle Zhang; Guangyi Wang; Guangyi Wang (Frontiers in Microbiology, 2017)
Qinhuangdao coastal waters in northern China are heavily impacted by anthropogenic and natural activities, and we anticipate a direct influence of the impact on the bacterioplankton abundance and diversity inhabiting the adjacent coastal areas. To ascertain the anthropogenic influences, we first evaluated the seasonal abundance patterns and diversity of bacterioplankton in the coastal areas with varied levels of natural and anthropogenic activities and then analyzed the environmental factors which influenced the abundance patterns. Results indicated distinct patterns in bacterioplankton abundance across the warm and cold seasons in all stations. Total bacterial abundance in the stations ranged from 8.67 × 104 to 2.08 × 106 cells/mL and had significant (p < 0.01) positive correlation with total phosphorus (TP), which indicated TP as the key monitoring parameter for anthropogenic impact on nutrients cycling. Proteobacteria and Cyanobacteria were the most abundant phyla in the Qinhuangdao coastal waters. Redundancy analysis revealed significant (p < 0.01) influence of temperature, dissolved oxygen and chlorophyll a on the spatiotemporal abundance pattern of α-Proteobacteria and Cyanobacteria groups. Among the 19 identified bacterioplankton subgroups, α-Proteobacteria (phylum Proteobacteria) was the dominant one followed by Family II (phylum Cyanobacteria), representing 19.1–55.2% and 2.3–54.2% of total sequences, respectively. An inverse relationship (r = -0.82) was observed between the two dominant subgroups, α-Proteobacteria and Family II. A wide range of inverse Simpson index (10.2 to 105) revealed spatial heterogeneity of bacterioplankton diversity likely resulting from the varied anthropogenic and natural influences. Overall, our results suggested that seasonal variations impose substantial influence on shaping bacterioplankton abundance patterns. In addition, the predominance of only a few cosmopolitan species in the Qinhuangdao coastal wasters was probably an indication of their competitive advantage over other bacterioplankton groups in the degradation of anthropogenic inputs. The results provided an evidence of their ecological significance in coastal waters impacted by seasonal inputs of the natural and anthropogenic matter. In conclusion, the findings anticipate future development of effective indicators of coastal health monitoring and subsequent management strategies to control the anthropogenic inputs in the Qinhuangdao coastal waters.